2009
DOI: 10.1080/00140130802707907
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breast support on kinetics during overground running performance

Abstract: Changes in ground reaction forces that result from different breast support conditions may have implications for sports performance and transmission of forces through the skeleton. The aim of this investigation was to compare kinetic variables and breast motion in a no-bra, everyday-bra and two sports-bra conditions. Following ethical approval, eight female participants with D-cup breasts had retro-reflective markers placed on the left and right nipples, anterior superior iliac spines and clavicles. Five calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 8 publications
5
84
4
1
Order By: Relevance
“…It is suggested that the decrease in pectoralis major and deltoid activity reported in the high breast support may be due to less tension within the upper body when running with superior breast support, due to the significant reduction in breast pain. In line with previous literature (Mason et al, 1999;McGhee, Power, & Steele, 2007;Scurr, White, et al, 2010;McGhee et al, 2012;White et al, 2009), exercise related breast pain was significantly greater in the bare-breasted trial and low breast support than the high breast support. However, the pectoralis major muscle activity was greater within the lower breast support conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is suggested that the decrease in pectoralis major and deltoid activity reported in the high breast support may be due to less tension within the upper body when running with superior breast support, due to the significant reduction in breast pain. In line with previous literature (Mason et al, 1999;McGhee, Power, & Steele, 2007;Scurr, White, et al, 2010;McGhee et al, 2012;White et al, 2009), exercise related breast pain was significantly greater in the bare-breasted trial and low breast support than the high breast support. However, the pectoralis major muscle activity was greater within the lower breast support conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The greatest movement of the breast during running was expected and reported within the barebreasted condition Scurr, White, et al, 2010;White, Scurr, & Smith, 2009). Within the current study, the increase in pectoralis major activity during the bare-breasted condition is of interest.…”
Section: Discussionmentioning
confidence: 81%
“…When no bra was used, markers were positioned on the right nipple, and the suprasternal notch (the junction of the sternum and the clavicles). When a bra was worn, the nipple marker was repositioned on the bra over the nipple with the assumption that there was no relative motion between the bra surface and the skin [6,[19][20][21][22][23]. The global coordinate system was defined with respect to the laboratory with the positive vertical coordinate in the upward direction and co-ordinates were measured to an accuracy of ±0.25 mm.…”
Section: Laboratory Set-upmentioning
confidence: 99%
“…This renders it understandable that D-cup subjects have been selected as the focus of many studies McGhee et al, 2013;. Vertical displacement has been confirmed to be greatest during running and jogging (Mason et al, 1999;Scurr et al, 2009;White et al, 2009) , and showed that pert and ptotic breasts move in different patterns, with more anterior and medial movement occurring in the ptotic breasts. With insufficient support, large-breasted women tend to experience ptosis, and consequently, the larger breast movement contributes to breast pain.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the impact of three types of bra (crop-top, everyday bra, and sports bra). Previous research analyzing bra-breast motion has adopted optical tracking systems to capture the motion of the nude breast and breasts supported by sports bras White et al, 2009White et al, , 2011Mason et al, 1999;. These motion data were collected and further analyzed under the assumption that no breast-bra relative movement occurred within the bra.…”
Section: Introductionmentioning
confidence: 99%